GDI (IoT-Based Gas Detector) As an Appropriate Technology for Gas Leak Detection in Tarakan City, North Kalimantan: GDI (Gas Detector Based Internet of Things (IoT)) - Putra Siregar, Muhammad Abrar; Andyna Maharani, Cinta Naswa; Nilogiri, Agung; YAP, Ferdianto (Inovbook Publications, 2024)
Tarakan City, as the center of oil and gas resource exploitation in North Kalimantan Province, faces significant challenges related to safety and security concerning potential natural gas leaks. With its large population and the presence of 1,400 oil and gas wells, as well as being the largest consumer of natural gas networks in Indonesia with 32,000 consumers, the risk of gas leaks is a major concern. Previous gas leak incidents have demonstrated serious impacts, including fires and explosions resulting in significant losses for the community and the environment. To address these challenges, the 5.0 technology offers a potential solution, particularly implementing the Internet of Things (IoT). Based on this technology, developing an IoT-Based Gas Detector involves surveying potential tools, analyzing economic, social, and environmental factors, assembling the tools, and applying the product. IoT Gas Detectors have an advantage by utilizing connected sensor technology. The IoT-Based Gas Detector can be utilized to detect gas leaks in real-time, providing swift responses and reducing the potential impacts of gas leaks. Consequently, it can increase safety, security, and the efficient use of natural resources. The IoT-based Gas Detector (GDI) program supports several Sustainable Development Goals (SDGs), including: [1] No Poverty, [3] Good Health and Well-being, [7] Affordable and Clean Energy, [9] Industry, Innovation, and Infrastructure, [11] Sustainable Cities and Communities, [17] Partnerships for the Goals.